A combined uninterruptible power supply and dynamic voltage compensator using a flywheel energy storage system. - Weissbach, R.S (IEEE Transactions on power delivery)
Due to technological advancements, the flywheel energy storage system is becoming a viable alternative to electrochemical batteries. Two potential applications of flywheel systems are for voltage support and as an uninterruptible power supply. The two applications are both useful to protect critical loads on distribution feeders. Therefore, it may be useful to look at the possibility of combining both functions into one system. This paper considers a flywheel energy storage system which performs both functions and presents a novel control scheme using both sinusoidal pulse width modulation as well as a boost converter to regulate the critical load voltage on the feeder. Dynamic voltage compensation is achieved by injecting voltage through series transformers rather than by connecting the system in shunt, to minimize the amount of kVA required by the flywheel system. Simulations are provided using the Electromagnetic Transients Program to validate the concept